2020
DOI: 10.1002/jsfa.10322
|View full text |Cite
|
Sign up to set email alerts
|

Association between a low‐carbohydrate diet and sleep status, depression, anxiety, and stress score

Abstract: BACKGROUND Dietary intakes, especially carbohydrates, play an important role in blood glucose control in patients with diabetes. It is suggested that carbohydrate amounts may be effective in diabetes complications. This study aimed to reveal the association of low‐carbohydrate diet (LCD) and sleep and mental status among patients with diabetes. METHODS This cross‐sectional study was conducted among 265 women with type 2 diabetes. Anthropometric measures, as well as biochemical tests, were recorded. Dietary int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 42 publications
5
33
2
2
Order By: Relevance
“…Depression has been one of the important complications of diabetes. In order to investigate the relationship between LCD and mental status, T2DM cases were assessed by a questionnaire for taking food and by the depression, anxiety, and stress scale [34]. As a result, cases in the highest quartile of LCD score showed a 69% lower risk of poor sleep, and a 73% lower risk of anxiety compared with those in the lowest quartile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression has been one of the important complications of diabetes. In order to investigate the relationship between LCD and mental status, T2DM cases were assessed by a questionnaire for taking food and by the depression, anxiety, and stress scale [34]. As a result, cases in the highest quartile of LCD score showed a 69% lower risk of poor sleep, and a 73% lower risk of anxiety compared with those in the lowest quartile.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, cases in the highest quartile of LCD score showed a 69% lower risk of poor sleep, and a 73% lower risk of anxiety compared with those in the lowest quartile. Consequently, T2DM patients with LCD meals seem to have better sleep conditions and less mental disorders [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, shifting the main calorie intake to the end of the day adversely affects digestion and makes sleep difficult due to GI symptoms such as gastro-esophageal reflux (GERD), dyspepsia, and nausea; more so if the meal is abundant and fat-rich [28]. Conversely, the role of carbohydrates on sleep patterns is still debated [29,30] and the weight of carbohydrates versus caloric load is controversial.…”
Section: Nutrition and Sleep Disordersmentioning
confidence: 99%
“…Several studies were performed regarding relation between LCD and risk of chronic disease such metabolic syndrome [12,24,25], diabetes [19,26], cardiovascular disease [20,27], and cancer [28,29]. Nevertheless, a few studies especially large scale studies have been evaluated association between LCD and psychological disorders and their findings were inconsistence [23,[30][31][32][33]. One research did not find any significant association between LCD score and psychological disorders (depression, anxiety and psychological distress) in a sample of Iranian adults [23], while the findings of other studies indicated a protective effect of this dietary pattern on depression in diabetic women [30] and overweight or obese women [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a few studies especially large scale studies have been evaluated association between LCD and psychological disorders and their findings were inconsistence [23,[30][31][32][33]. One research did not find any significant association between LCD score and psychological disorders (depression, anxiety and psychological distress) in a sample of Iranian adults [23], while the findings of other studies indicated a protective effect of this dietary pattern on depression in diabetic women [30] and overweight or obese women [31,32]. More adherence to LCD was also associated with reduced chance of anxiety among diabetic women [30], overweight or obese women [32] and as well as stress in a sample of Iranian nurses [33].…”
Section: Introductionmentioning
confidence: 99%